USING HEALTH – PROTECTING TECHNOLOGIES TO ENHANCE THE LOGICAL THINKING OF LEARNERS IN ENGLISH CLASSES - Toshtemirova Kamola Absattarovna (International Engineering Journal For Research & Development, 2021)
This article analyzes the usage of health-protecting technologies, in particular teaching English and enhancing logical thinking through fairy-tales and riddles.